PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this article, the authors highlight the pedagogical conditions for the development of professional competence of future teachers, the concept of competence, the structural foundations of pedagogical professional competence.